NR2F1 database: 112 variants and 84 patients support refining the clinical synopsis of Bosch–Boonstra–Schaaf optic atrophy syndrome. Issue 2 (9th December 2021) - Billiet, Benjamin; Amati‐Bonneau, Patrizia; Desquiret‐Dumas, Valérie; Guehlouz, Khadidja; Milea, Dan; Gohier, Philippe; Lenaers, Guy; Mirebeau‐Prunier, Delphine; den Dunnen, Johan T.; Reynier, Pascal; Ferré, Marc
Abstract: Pathogenic variants of the nuclear receptor subfamily 2 group F member 1 gene ( NR2F1 ) are responsible for Bosch–Boonstra–Schaaf optic atrophy syndrome (BBSOAS), an autosomal dominant disorder characterized by optic atrophy associated with developmental delay and intellectual disability, but with a clinical presentation which appears to be multifaceted. We created the first public locus‐specific database dedicated to NR2F1 . All variants and clinical cases reported in the literature, as well as new unpublished cases, were integrated into the database using standard nomenclature to describe both molecular and phenotypic anomalies. We subsequently pursued a comprehensive approach based on computed representation and analysis suggesting a refinement of the BBSOAS clinical description with respect to neurological features and the inclusion of additional signs of hypotonia and feeding difficulties. This database is fully accessible for both clinician and molecular biologists and should prove useful in further refining the clinical synopsis of NR2F1 as new data is recorded. Abstract : Pathogenic variants of the nuclear receptor subfamily 2 group F member 1 ( NR2F1 ) gene are responsible for Bosch–Boonstra–Schaaf optic atrophy syndrome (BBSOAS), an autosomal dominant disorder characterized by optic atrophy associated with developmental delay and intellectual disability, but with a clinical presentation which appears to be multifaceted. We created the first public locus‐specific database dedicated to NR2F1 by adopting a comprehensive approach based on computed representation and analysis that led to suggest a refinement of the BBSOAS clinical description.